Frontal alpha asymmetry and sexually motivated states. (27th January 2014) - Prause, Nicole; Staley, Cameron; Roberts, Verena
Abstract Anterior alpha asymmetry of electroencephalographic (EEG) signals has been suggested to index state approach (or avoidance) motivation. This model has not yet been extended to high approach‐motivation sexual stimuli, which may represent an important model of reward system function. Sixty‐five participants viewed a neutral and a sexually motivating film while their EEG was recorded, and reported their sexual feelings after each film. Greater alpha power in the left hemisphere during sexually motivated states was evident. A positive relationship between self‐reported mental sexual arousal and alpha asymmetry was identified, where coherence between these indicators was higher in women. Notably, coherence was stronger when mental versus physical sexual arousal was rated. Alpha asymmetry appears to offer a new method for further examining this novel coherence pattern across men and women.